RELASI GENDER DALAM PENDIDIKAN ISLAM ( Analisis Pendidikan Islam Menurut Al Ghazali ) - Mutamakin Mutamakin (Ta`Limuna: Jurnal Pendidikan Islam, 2012)
Gender is a cultural concept that try to make distinction in role, attitude, mentality and emotional characteristic between male and female in society. In social structure that happen in society, in its history, female is located in minority position. Meanwhile, status differentiation in relation to sex is not a universal thing. Female is located in inferior position. Their role is limited, so that the access to gain power is also limited too, as consequence, female get lower status than male. The Koran admits that there is differentiation in biological anatomy, but this condition is not made as right reason to differentiate one sex to another. Koran doesn’t give gender burden and give an absolute and stiff values to someone, but how to make it able to help human to gain noble aims in world and heaven. This happiness lives here and after are as a main principle of al-Ghozali education.